Sustainability Information Provision (SIP) framework: A review of the promotion of sustainability in the residential sector. (1st February 2023) - Rashed, Yussra; Omrani, Sara; Nilsson, Danie; Drogemuller, Robin
Abstract: Carbon emissions reduction and resource preservation targets dictate a global transition toward sustainability in all industries. However, achieving the required sustainability goals in the building sector is hindered by the current suboptimal awareness of sustainability in the market, particularly for residential buildings. A prime reason for the lack of effectiveness of sustainability as a factor in dwelling selection is the sustainability "information asymmetry". The information regarding the sustainability performance of buildings provided to residential buyers and end-users is minimal compared to the wealth of information available analysis tools can generate. Numerous research efforts highlight the downsides of sustainability information asymmetry, yet strategies for improvement remain under-addressed. This paper critically reviews the literature on sustainability information asymmetry in the residential sector and presents a Sustainability Information Provision framework. The critical analysis presents an overview of the status of "information asymmetry" and identifies barriers and success criteria for the adequate provision of sustainability information. A Sustainability Information Provision Framework is formulated from these findings to assist residential building researchers and providers, such as developers and designers, in identifying and preparing relevant sustainability information for buyers and end-users. This research is also a necessary precursor to the development of additional policies on the provision of sustainability information, as policy development requires frameworks and tools to support policy implementation. Improving sustainability information provision is a crucial initial step toward raising market awareness and interest in sustainability, with the ultimate goal of improving the market penetration of sustainable residential buildings. Highlights: Explored sustainability promotion in dwellings through information provision. Developed a framework for dwellings sustainability information provision. Identified three categories of barriers to sustainability information provision. Identified key success criteria to inform buyers and end-users about sustainability.